The end of empire: new radiocarbon dates from the Ayacucho Valley, Peru, and their implications for the collapse of the Wari State - Finucane, Brian Clifton; Valdez, J. Ernesto; Calderon, Ismael Perez; Pomacanchari, Cirilo Vivanco; Valdez, Lidio M. (My University, 2007)
This paper presents a suite of new accelerator mass spectrometry (AMS) radiocarbon measurements from the Ayacucho Valley of Peru and discusses their implications for the timing and nature of the collapse of the Wari Empire. Analysis of these and previously published dates from the region indicate that there is little evidence for state political authority in Ayacucho prior to the end of the 7th century. Dated human remains from the polity’s eponymous capital indicate that the authority of the state’s rulers persisted at least as late as the mid-11th century. Dates from rural sites in the Ayacucho Valley suggest continuity of occupation and folk material culture following Wari’s disintegration. Finally, AMS measurements of bone from 2 large extramural ossuaries represent the first absolute dates associated with Chanca ceramics and suggest that this archaeological/ethnohistoric culture appeared in the valley at about AD 1300.
Keywords: Wari; Ayacucho Valley; Peru